Исследование устройства контроля короткозамкнутой обмотки ротора асинхронного двигателя - Васьковский, Ю.Н.; Коваленко, М.А. (Електротехніка і електромеханіка, 2011)
A device for control and diagnostics of the rotor short-circuited winding in an asynchronous motor under its repair is offered. A field mathematical model is developed; the device sensitivity is investigated for motors of different power and with different rotor tooth-slot area configuration.